A New Lignan from the Fruit of Schisandra propinqua var. propinqua and its Anti-HIV Activity - FAN , PENG; ZHANG , XIN; LI , TAO; DAI , YUN; LI , GAN-PENG; HU , QIU-FEN (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the fruit of Schisandra propinqua var. propinqua led to the isolation and identification of a new lignan named Schproplignan C. It structure was elucidated by spectroscopic methods including extensive 1 D- and 2 D-NMR techniques and its HIV-1 activity was evaluated. It shows an anti-HIV activity with EC50 (median effect concentration) value of 8.26 mg/mL and a therapeutic index (TI) above 22.8.